Gestión de inventarios en la Ferretería Don Pini de la ciudad de Babahoyo en el año 2020 - Vargas Nazareno, Melisa Xiomara (2021)
The case study was carried out at the Don Pini Hardware Store in the city of Babahoyo to raise awareness of the difficulties or delimitations it currently presents in the field of inventory management. This research was carried out under parameters or methods that we implemented to collect the information and develop the case. According to those investigated in this case study we were able to obtain results through the problems related to the case such as: the lack of sales projection, the poor supply of inventories, failure to control the existence, the log turnover of products, the lack of advertising strategy, the lack of customer service deficiency, limited space, among others.